Information Revelation and Principal-Agent Contracts - Alvi, Eskander (Journal of Labor Economics, 1988)
In an environment in which effort is private information to the worker, agreements between a risk-neutral principal and a risk-averse agent are likely to be risk-sharing and information-revealing mechanisms. It is shown that principal-agent contracts have significant implications for both compensation and employment rules in a simple work-sharing model. In general, such contracts involve incomplete income insurance and involuntary or excessive underemployment. This supports the view that models of worker-specific information, particularly with moral hazard, provide a natural explanation of underemployment.